The Roles of Ambassadresses in Early Modern Diplomacy: The Promise of Digitised Seventeenth-Century Dutch Newspapers - Lamal, Nina (Early Modern Low Countries, 2025)
Despite a recent surge in scholarship recognising the vital role of women in early modern diplomacy, the role of women in Dutch seventeenth-century embassies has been completely overlooked. This significant blind spot in Dutch scholarship skews our view of how the Dutch Republic, a new player on the international stage, practiced its diplomacy. This essay focuses on the role of ambassadresses, the wives of ambassadors, who joined their husband on a diplomatic mission. More specifically, it explores the potential of using digitised seventeenth-century Dutch newspapers as a valuable resource for finding more material to research the role of diplomats’ wives in shaping Dutch and European diplomacy.